Resolution of Membranous Glomerulopathy after pregnancy: An interesting case report. - Dilawar, Mubashir; Sabir, Omer; Basit, Bilal (Pakistan Journal of Kidney Diseases, 2024)
Proteinuria before twenty weeks of gestation should always be evaluated as it can be due to underlying glomerular diseases. We present a case of membranous nephropathy during pregnancy diagnosed by kidney biopsy and negative PLA2r aantibodies. Therapy was initiated with prednisolone 60mg per day. Calcineurin Inhibitor was also later started. Termination of Pregnancy when worsening of proteinuria was observed on followup. Patient achieved partial remission after two weeks and complete remission after one and half month of termination of pregnancy.